The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1021/acs.jafc.2c06185
|View full text |Cite
|
Sign up to set email alerts
|

Screening UDP-Glycosyltransferases for Effectively Transforming Stevia Glycosides: Enzymatic Synthesis of Glucosylated Derivatives of Rubusoside

Abstract: Five plant-derived uridine diphosphate glycosyltransferases (UGTs) that catalyzed the glucosylation of stevia glycosides (SGs) were uncovered as the result of sequence mining considering the catalytic residues and conserved motifs of the known UGTs. Thereinto, LbUGT from Lycium barbarum with high activity toward rubusoside has been enzymatically characterized. The recombinant LbUGT was demonstrated to catalyze the β-1,6-glucosylation at C19 of rubusoside, producing a monoglucosyl derivative 13-[(O-β-D-glucopyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…The transglycosylation rate of stevioside could reach 85.6% in the end. More lately, it is also observed that efforts were made to screen different glycosyltransferase enzymes to ultimately increase sweetness intensity and reduce bitter taste (Pan et al , 2022).…”
Section: Functionsmentioning
confidence: 99%
“…The transglycosylation rate of stevioside could reach 85.6% in the end. More lately, it is also observed that efforts were made to screen different glycosyltransferase enzymes to ultimately increase sweetness intensity and reduce bitter taste (Pan et al , 2022).…”
Section: Functionsmentioning
confidence: 99%
“…However, the diversity of glycosylation sites leads to variations in the biological activities and functions of glycoside products . When polyphenols are used as aglycone acceptors, chemical glycosylation requires cumbersome protection/deprotection steps to achieve high regioselectivity. , Therefore, the enzymatic glycosylation of polyphenols offers numerous advantages, including precise tuning of regioselectivity, adherence to green chemistry principles, and high efficiency. UGTs from various species, including Arabidopsis thaliana, Vitis vinifera, and Streptomyces antibioticus, have been extensively characterized. Indeed, most of the characterized UGTs, including UGT BL 1, exhibit poor regioselectivity and catalytic activity. Simultaneous improvements in the catalytic efficiency and regioselectivity of UGTs remain a challenge.…”
Section: Introductionmentioning
confidence: 99%